"The Fitness of Their Union": Travel and Health in the Letters of Humphry and Jane Davy. (3rd July 2019) - Golinski, Jan
Abstract : The letters of Humphry Davy and his circle, to be published shortly, shed new light on his marriage to Jane Apreece. This paper examines the journeys undertaken by the couple, together and separately, with particular attention to the therapeutic benefits they sought from travel. I argue that their increasingly divergent itineraries reflected a growing understanding that Humphry and Jane had different humoral temperaments or constitutions, leading them to seek different climatic conditions to cure their ailments. While Jane's temperament was classified as melancholic, requiring her to travel to warmer and sunnier climes during the English winter, Humphry's was believed to be sanguine, meaning he had to avoid excessive heat along with stimulating food and drink. He relied on classical ideas about individuals' different humoral constitutions, and the therapies appropriate to them, while measuring atmospheric variables to determine the best places to restore his health. The Davys' letters reveal the beliefs about bodily differences and atmospheric conditions that shaped their therapeutic travels.